The Role of Village Government in Improving Farmers’ Welfare Through Infrastructure Development in Ciwangi Village, Garut Regency - Wijaya, Zein Maulidan Aditya; Halimah, Mas (Jurnal Kebijakan Pembangunan, 2024)
This research studies the role of the Ciwangi Village Government in improving farmers' welfare through infrastructure development. The village faces various challenges in community welfare, with families struggling to meet basic needs and self-actualization, and individuals failing to fully realize their potential. This research aims to analyze the role of the government in achieving such goals. Using a qualitative method with a descriptive approach, this research seeks to understand, analyze, and explain various aspects of the village government's involvement. In addition, in this study, there are 3 stages of qualitative data analysis, namely data condensation, data presentation, and conclusion drawing. The results show that the Village Government seeks to improve the welfare of farmers by building special roads for agriculture, thus facilitating farmers' access to market their agricultural products. The government adopts a participatory approach in carrying out its role as a problem solver, facilitator, inter-system liaison, motivator, and communicator to improve farmers' welfare.